Muscle stiffness - Thompson, Philip D.; Meinck, Hans-Michael (Neurological disorders, 2003)
This chapter reveals that muscle stiffness and cramps are common complaints that may arise from the central or peripheral nervous system. Within this large differential diagnosis, many conditions have additional features that provide valuable diagnostic clues. Accordingly, the assessment of these symptoms requires a detailed history and careful physical examination. Central nervous system diseases such as those affecting the basal ganglia produce rigidity and muscle spasm as one part of a syndrome of dystonia and parkinsonism. The rigidity of parkinsonism is accompanied by hypokinesia and bradykinesia of voluntary hand and finger movements, walking, and axial movement. In addition there is a reduction in automatic movements such as facial expression when talking and arm swing during walking. In dystonia, rigidity and spasm diminish at rest and disappear during sleep. The increase in muscle tone and abnormal postures of dystonia typically occurs on action, varies during movement, and subsides with rest.
Available online 9 May 2007
Gesehen am 01.03.2021